Differences in body composition and physical functions associated with sarcopenia in Chinese elderly: Reference values and prevalence. Issue 1 (January 2015) - Zeng, Ping; Wu, Sinan; Han, Yiwen; Liu, Jingmin; Zhang, Yi; Zhang, Enyi; Zhang, Yan; Gong, Huan; Pang, Jing; Tang, Zhili; Liu, Hongxing; Zheng, Xiuyuan; et al.
Highlights We investigate the age-related differences in skeletal muscle mass (SM), muscle strength and physical performance in mainland Chinese. We explore reference values (criteria) for the definition of sarcopenia in elderly Chinese. Apply our suggested criteria and consensus criteria (Asia, European and international) to the study population; it results in 2–4 times difference in the prevalence of sarcopenia features. These findings indicate that it is necessary to establish an outcomes-based and ethnic-specific set of reference values for the diagnosis of sarcopenia in elderly Chinese.